Palladium-Catalyzed Arylation of Aromatic Amides Directed by a [4-Chloro-2-(1H-pyrazol-1-yl)phenyl]amine Auxiliary - Hu, Ya-Hua; Xu, Zhi; Shao, Ling-Yan; Ji, Ya-Fei (Synlett, 2018)
A palladium-catalyzed ortho-arylation of aromatic amides directed by [4-chloro-2-(1H-pyrazol-1-yl)phenyl]amine as a bidentate auxiliary has been established. The reaction is characterized by normal working conditions, a broad substrate scope, and a wide functional-group tolerance. In particular, the protocol is compatible with highly sterically demanding ortho-substituted anilides and aryl iodide partners, with good yields.
Keywords: C–H activation; arylation; amides; directing groups; palladium catalysis; biaryls